Teaching reading with heart: a mixed-methods examination of university teacher-student relationships and their impact on elementary teacher candidates’ self-determination in reading methods - Maydew, Savannah Sage (My University, 2025)
This dissertation examines the impact of university teacher-student relationships on the self-determination of elementary teacher candidates in reading methods courses. Grounded in Self-Determination Theory (Deci & Ryan, 1980), this study explores how faculty interactions support autonomy, competence, and relatedness—three psychological needs essential for motivation and professional development. The research addresses one primary question and two supporting questions: (R1) How do university teacher-student relationships impact elementary teacher candidates' self-determination in reading methods courses? (R1a) What specific behaviors and interactions characterize positive teacher-student relationships in this context? (R1b) How do university teacher-student relationships foster a sense of autonomy, influence perceptions of competence, and affect overall self-determination? This mixed-methods study integrates quantitative survey data and qualitative interviews with elementary teacher candidates enrolled in reading methods coursework at a Kansas Board of Regents institution. The study uses descriptive and correlation statistics in SPSS to analyze survey responses and applies open, axial, and selective coding to interview transcripts to identify emergent themes. Findings indicate that faculty approachability, responsive feedback, mentorship, and instructional modeling significantly influence teacher candidates’ self-determination. The study introduces the HEART Model (Maydew, 2025, forthcoming), a conceptual framework that identifies five key dimensions of effective teacher-student relationships: holistic support, enthusiastic engagement, approachability, responsive feedback, and transformative teaching. This model offers a structured approach to enhancing faculty-student interactions in teacher education. The implications of this study extend to teacher education programs, faculty training, and institutional policies. By fostering relationally supportive teaching practices, universities can help teacher candidates develop confidence, motivation, and instructional competence. These findings underscore the importance of embedding faculty-student relationships into teacher preparation curricula and accreditation frameworks, ensuring that future educators receive both content knowledge and relational support necessary for professional success.
Keywords: Teacher-student relationships; Self-Determination Theory; Teacher preparation; Reading methods; Mixed-methods research; Faculty support in higher education